2021
DOI: 10.3390/nano11041012
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Mechanical, Thermal and Antimicrobial Properties of Additively Manufactured Polylactic Acid with Optimized Nano Silica Content

Abstract: The scope of this work was to create, with melt mixing compounding process, novel nanocomposite filaments with enhanced properties that industry can benefit from, using commercially available materials, to enhance the performance of three-dimensional (3D) printed structures fabricated via fused filament fabrication (FFF) process. Silicon Dioxide (SiO2) nanoparticles (NPs) were selected as fillers for a polylactic acid (PLA) thermoplastic matrix at various weight % (wt.%) concentrations, namely, 0.5, 1.0, 2.0 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…The exceptions are composites obtained by the injection method PC/3%S and PC/3%L, which had better impact resistance (Figure 7b). It should be mentioned that analogous results of impact tests for composites containing selected fillers are described in the literature [43,44]. Based on the results of the impact tests, it was found that both the content and the type of filler had an effect on the tested property.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…The exceptions are composites obtained by the injection method PC/3%S and PC/3%L, which had better impact resistance (Figure 7b). It should be mentioned that analogous results of impact tests for composites containing selected fillers are described in the literature [43,44]. Based on the results of the impact tests, it was found that both the content and the type of filler had an effect on the tested property.…”
Section: Resultsmentioning
confidence: 66%
“…The exceptions posites obtained by the injection method PC/3%S and PC/3%L, which had bette resistance (Figure 7b). It should be mentioned that analogous results of impact composites containing selected fillers are described in the literature [43,44]. The morphology of brittle fractures of the obtained composites was analyzed using scanning electron microscopy (SEM).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…However, they may induce some processability issues to the FFF 3D melt filamentous printing process. This is due to the well-known abrupt increase of the polymer melt viscosity, associated with the nanoparticle inclusions hindering the polymer chain mobility in the melt state, which may result in a deteriorated quality of the 3D printed final objects [ 17 , 18 , 19 , 20 ]. It is of great scientific interest thus to develop polymer (nano-)composites able to be processed through AM technologies without compromising mechanical, thermal and other inherent properties of the matrix host material [ 6 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Silicon dioxide is also utilized as filler in polymer-based composites [ 30 , 31 , 32 , 33 ]. Targeting to increase microwave absorption, antimicrobial performance, mechanical properties, etc., silica can be used as a dispersed phase in polymeric materials [ 20 , 34 ]. In many cases SiO 2 is also accrued as to improve processability of polymers in different manufacturing methods [ 20 , 35 ].…”
Section: Introductionmentioning
confidence: 99%